2012
DOI: 10.1590/s1413-35552012005000044
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre sarcopenia, obesidade sarcopênica e força muscular com variáveis relacionadas de qualidade de vida em idosas

Abstract: Objective: To investigate the association between sarcopenia, sarcopenic obesity and muscle strength and variables related to quality of life in elderly women. Method: The sample consisted of 56 female volunteers who underwent body composition analysis (BMI and x-ray absorptiometry dual-energy DXA). Handgrip strength was measured using a Jamar dynamometer. We used the SF-36 health questionnaire to analyze quality of life. The data were analyzed with descriptive statistics and the Pearson correlation coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 41 publications
2
18
0
5
Order By: Relevance
“…In concordance with a recent Brazilian study of older women, we found that SO is associated with reduced grip strength [ 1 ]. Two additional studies support our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In concordance with a recent Brazilian study of older women, we found that SO is associated with reduced grip strength [ 1 ]. Two additional studies support our results.…”
Section: Discussionsupporting
confidence: 92%
“…Aging is a continuous process that involves physiological changes in multiple body systems resulting in reduced functional capacity [ 1 ]. The musculoskeletal system, involving bodily functions such as muscle contraction, movement and locomotion, is affected by loss of lean mass, particularly muscle mass (sarcopenia) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…2. Briefly, 9 studies explored the role of biological and lifestyle factors in the [56,87,101], balance (1 study) [94], risk (1 study) [93] or fear (1 study) [31] of falling], musculoskeletal disorders [bone health (1 study) [94], fractures (1 study) [92], osteoarthritis (1 study) [66], osteoporosis (2 studies) [46,92]], mental health [depression (1 study) [55] and psychological health (1 study) [45]], low quality of life (3 studies) [40,45,99], hospitalization (1 study) [87] and risk of mortality (4 studies) [33,38,52,75]. Finally, 6 studies tested clinical interventions in sarcopenic obesity populations including exercise training to improve physical function (3 studies) [36,44,69], effects of exercise and nutrition on recovery from sarcopenic obesity (2 studies) [58,80] and protein intake for the prevention of lean-mass loss in older individuals (1 study) [78].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The definition of sarcopenic obesity in the majority of the studies (66 studies) was based on the co-existence of obesity and sarcopenia (used as a synonymous of low or reduced skeletal muscle mass), which were regarded as two distinct categories ( Table 2). Less frequently (only 3 studies [50,81,99]) sarcopenic obesity was defined by calculating the population distribution of the residuals of linear regression models applied to predict appendicular fat-free mass (AFFM) using independent variables such as height (in meters) and fat-mass (FM) (in kg). Two studies used the FM to FFM or the visceral adipose tissue area to thigh muscle area ratios to identify cases of sarcopenic obesity [41,70].…”
Section: Definitions Of Sarcopenic Obesitymentioning
confidence: 99%
“…To this set of aspects, which involve a sequence of aging processes, the "biological fragility syndrome", here called fragility is conditioned. [1][2] Fragility is represented as an important public health problem and its development is understood as arising from the interaction of biological, psychological, cognitive and social factors throughout life and with potential for the prevention, identification and treatment of symptoms. The prevalence of fragility is approximately 6.9% in the elderly living in the community surrounding the FHU and this frequency tends to increase with increasing age.…”
mentioning
confidence: 99%